2019
DOI: 10.1002/nop2.379
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with subsequent diabetes‐related self‐care activities: The role of social support and optimism

Abstract: AimThis study aimed to explore how social support (external factor), optimism (internal factor) and their interaction associated with diabetes‐related self‐care activities (DRSCA) over 3 months among people with type 2 diabetes mellitus (T2DM).DesignBoth questionnaire‐based and telephone‐based survey were used. The data were collected face to face, the first time by questionnaire and the second time by telephone.MethodsOne hundred and fifty‐five patients completed valid survey questionnaires (response rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Owing to a cross‐sectional design, convenience sampling was used from two hospital in Tianjin, China, which could lead to sampling bias and might not be generalized to populations of other geographic regions. In addition, self‐report measures could appear to be response bias, that is, deviation caused by the psychological or personality disposition of the respondents (Zhao et al., 2019 ). Despite the limitations, self‐report measure is one of the most feasible methods for data collection (Stirratt et al., 2015 ).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to a cross‐sectional design, convenience sampling was used from two hospital in Tianjin, China, which could lead to sampling bias and might not be generalized to populations of other geographic regions. In addition, self‐report measures could appear to be response bias, that is, deviation caused by the psychological or personality disposition of the respondents (Zhao et al., 2019 ). Despite the limitations, self‐report measure is one of the most feasible methods for data collection (Stirratt et al., 2015 ).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Previous studies revealed that high level of social support could improve chronic illness self-management behaviour (Zhao et al, 2019). Successful CHD self-management needs social support from families, friends and doctors, in addition to patient's own efforts.…”
mentioning
confidence: 99%
“…Compared to single people, marriage offers an environment of continuous and lasting support, which can promote physical and mental health. Also, frequent contact with family and friends is associated with positive self-care behaviors and adherence to treatment (14) .…”
Section: Discussionmentioning
confidence: 99%